FEATURES OF SCABIES AND NEW APPROACHES TO ITS DIAGNOSIS AND TREATMENT IN THE REGION OF ANDIJAN (World Bulletin of Public Health, 2024)
The article presents a review of domestic and foreign medical literature, reflecting the current state of epidemiology, various clinical forms of scabies and the reasons for failures in its treatment.